2023
DOI: 10.3390/ijms24044188
|View full text |Cite
|
Sign up to set email alerts
|

α1-Adrenergic Receptors: Insights into Potential Therapeutic Opportunities for COVID-19, Heart Failure, and Alzheimer’s Disease

Abstract: α1-Adrenergic receptors (ARs) are members of the G-Protein Coupled Receptor superfamily and with other related receptors (β and α2), they are involved in regulating the sympathetic nervous system through binding and activation by norepinephrine and epinephrine. Traditionally, α1-AR antagonists were first used as anti-hypertensives, as α1-AR activation increases vasoconstriction, but they are not a first-line use at present. The current usage of α1-AR antagonists increases urinary flow in benign prostatic hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 199 publications
0
4
0
Order By: Relevance
“…Emerging evidence implicates the importance of α 1 -ARs in the CNS, the cardiovascular, and the immune systems , and places them as potential therapeutic targets to treat various disorders. Subtype-selective α 1 -ARs ligands will be essential to study and fully exploit these receptors as therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence implicates the importance of α 1 -ARs in the CNS, the cardiovascular, and the immune systems , and places them as potential therapeutic targets to treat various disorders. Subtype-selective α 1 -ARs ligands will be essential to study and fully exploit these receptors as therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
“…Subtype-selective α 1 -ARs ligands will be essential to study and fully exploit these receptors as therapeutic targets. Despite decades of research, ligands highly selective for α 1B -AR are still lacking, and the physiological and pathophysiological roles of this receptor subtype remain incompletely understood. , While α 1B -AR is nonselectively targeted (along with α 1A -AR and α 1D -AR) in cardiovascular and genitourinary diseases, its role in other important organs where it is much more abundantly expressed (such as the brain, liver, ovaries, spleen, and kidney) remains to be explored. The discovery of a tool antagonist with greater than 10-fold selectivity for α 1B -AR over α 1A -AR and α 1D -AR would allow researchers to more confidently assign particular physiological actions of catecholamines to α 1B -AR stimulation specifically.…”
Section: Discussionmentioning
confidence: 99%
“…This cellular traffic is functional to maintain an efficient hematopoietic niche as well as to patrol the organism to ensure tissue homeostasis and an appropriate immunological reaction in case of infection. As the circadian control of HSC circulation is effective also when they are mobilized by colony stimulating factors [83], a higher number of HSCs could be harvested by apheresis if it were performed in humans at the beginning of the resting phase rather than in the morning. The number of HSCs is crucial for the success of HSC transplantation, thus this "circadian" procedure could be very useful.…”
Section: Discussionmentioning
confidence: 99%
“…They function through nine distinct human adrenergic receptor (AR) subtypes:and β-type (β 1 , β 2 , and β 3 ) 3,4 . Due to the lack of selective pharmacological agonists for α 1 -ARs, the therapeutic potential of α 1 -ARs has been largely unexplored [5][6][7][8][9] . However, mouse genetic studies with individual gene deletions have demonstrated distinct but overlapping physiological functions of α 1 -AR subtypes in the regulation of blood pressure, cardiac hypertrophy, vascular smooth muscle contraction, neurotransmission, learning and memory, and metabolism [10][11][12][13][14][15][16][17] .…”
mentioning
confidence: 99%